Konsep Perbandingan Harta dan Implikasinya dalam Ekonomi Islam - Endah Robiatul Adawiyah; Inayatul Ummah; Udin wahrudin (Mutawasith: Jurnal Hukum Islam, 2022)
The Paper is to study the Fikih Assets Comparison; Implications In The Islamic Economy. This research uses qualitative methods with a library study approach. in analyzing the position of property in Islamic economics that has a diversity of jurisprudence viewpoints. The discussion of property is considered important because all humans like property and there is a tendency to own property, the existence of property can harm or benefit humans depending on how they view the position of the treasure itself. The main contribution of this study concern on fill the gap how the concept of sharia economics in the professional persfection of jurispruding